Pengembangan Buku Panduan Mini Riset Mandiri Berbasis Keterampilan 4C untuk Mata Kuliah Reproduksi dan Embriologi Tumbuhan - Mike Dewi Kurniasih; Aprillyana Dwi Utami; Setiyo Prajoko; Azkia Salma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to develop a mini self-research guidebook based on 4C skills and determine the quality of the guidebook developed based on expert validation and trial results. The method used is RnD (Research & Development) using the ADDIE model. The developed guidebook was then assessed using a questionnaire instrument via google form by media experts, material experts and 28 Biology Education Study Program students. The results showed that the mini self-research guidebook product based on 4C skills was proven valid and feasible. This achievement is indicated by the results of the media expert validation assessment of 91.70% with very good and valid criteria; the material expert 95% with very good and valid criteria; and student responses of 89.02% with very good and valid criteria. In conclusion, the mini self-research guidebook based on 4C skills that were developed is classified as very good and valid and suitable to be used as a source of student self-study. Keywords: Guidebook, 4C Skills, 21st Century Skills, Mini Research